2009
DOI: 10.1215/15228517-2009-024
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of integrin αvβ3 expression in patients with malignant glioma by [18F] Galacto-RGD positron emission tomography

Abstract: Inhibitors targeting the integrin alpha(v)beta(3) are promising new agents currently tested in clinical trials for supplemental therapy of glioblastoma multiforme (GBM). The aim of our study was to evaluate (18)F-labeled glycosylated Arg-Gly-Asp peptide ([(18)F]Galacto-RGD) PET for noninvasive imaging of alpha(v)beta(3) expression in patients with GBM, suggesting eligibility for this kind of additional treatment. Patients with suspected or recurrent GBM were examined with [(18)F]Galacto-RGD PET. Standardized u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(123 citation statements)
references
References 24 publications
4
115
1
2
Order By: Relevance
“…2a). this is in contrast to observations noted in malignant gliomas by schnell et al (47) and in melanoma by albelda et al (48), who found that tumors expressed higher levels of αvβ3 than normal tissues. A statistically significant increased staining vs. controls was demonstrated for αvβ3 in endothelia, but not in stroma (tables iv and v).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…2a). this is in contrast to observations noted in malignant gliomas by schnell et al (47) and in melanoma by albelda et al (48), who found that tumors expressed higher levels of αvβ3 than normal tissues. A statistically significant increased staining vs. controls was demonstrated for αvβ3 in endothelia, but not in stroma (tables iv and v).…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies have found increased αvβ3 expression to be correlated with greater invasive or metastatic potential (53)(54)(55). Radiotracers specific to αvβ3 have revealed this integrin in human tumor tissue in situ (47,56). αvβ5 integrin has also been implicated in tumor cell invasion and migration (57)(58)(59), and αvβ3 and αvβ5 regulate cellular responses to hypoxia in glioblastomas (60).…”
Section: Discussionmentioning
confidence: 96%
“…c(RGDfK), a variant of the integrin antagonist Cilengitide, binds specifically to α v β 3 and α v β 5 integrins (33). c(RGDfK) was chosen for comparison because cyclic peptides containing an RGD motif have been evaluated as molecular imaging agents in numerous preclinical and clinical studies, including studies of human brain tumors (34). As with EETI 2.5F, these three peptides were labeled with AF680 such that one dye molecule was attached per peptide.…”
Section: Resultsmentioning
confidence: 99%
“…We realize that antiangiogenic therapy is more commonly used in other tumor types such as glioblastoma and breast cancer. However, in these malignancies a v b 3 integrins are frequently expressed on the surface of endothelial cells and related tumor cells (16,17). Therefore, it is challenging to monitor antiangiogenic therapies in these tumor types with RGD peptides.…”
Section: Discussionmentioning
confidence: 99%